Socioeconomic dynamics of beedi rolling in a Southern Indian state: implications for tobacco control - Praveen Kumar; Muralidhar M. Kulkarni; Eshwari K.; Yash Alok; Satish Kumar; Rohith Bhagawath; Radhika Nayak; Priyanka Bantwal; Ambigai Rajendran; Mark Goodchild; Praveen Sinha (Cogent Social Sciences)
This study aims to understand the work patterns and job-related challenges encountered by women who roll beedis, primarily from low-income households in India. Given the risks associated with beedi rolling and the government’s efforts to reduce tobacco use, this study sought to shed light on how these workers and their families may be impacted. Additionally, this study aims to investigate the effects of the COVID-19 pandemic on families dependent on beedi rolling on their livelihoods. Key insights were obtained through 14 semi-structured Focus Group Discussions with beedi rollers and 11 In-Depth Interviews with stakeholders comprising of government officials in three districts of coastal Karnataka between January and March 2023. The study identified two types of beedi rollers, registered and unregistered, who differed in payments and benefits. The varied responses to training programs on alternative livelihoods underscore the need government support to help individuals pursue and sustain alternative career options. The age limit for training under government schemes limits options for older rollers. Prominent issues include inadequate social security, limited access to government programs, and family vulnerability. This study highlights the need for comprehensive support for beedi rollers in coastal Karnataka, especially older rollers, and emphasizes the importance of tailored skill-development programs to improve their well-being.